Mild encephalopathy with reversible splenial lesion: An important differential of encephalitis. (May 2015) - Ka, Amy; Britton, Philip; Troedson, Christopher; Webster, Richard; Procopis, Peter; Ging, Joanne; Chua, Yew Wee; Buckmaster, Adam; Wood, Nicholas; Jones, Cheryl; Dale, Russell C.
Abstract Mild encephalopathy with a reversible splenial lesion (MERS) is a clinico-radiological syndrome characterized by a transient mild encephalopathy and a reversible lesion in the splenium of the corpus callosum on MRI. This syndrome has almost universally been described in children from Japan and East Asia. Here we describe seven cases of MERS occurring in Caucasian Australian children from one centre seen over a 3 year period. All patients had a fever-associated encephalopathy (n = 7), which presented with confusion (n = 4), irritability (n = 3), lethargy (n = 3), slurred speech (n = 3), drowsiness (n = 2) and hallucinations (n = 2). Other neurological symptoms included ataxia (n = 5) and seizures (n = 1). These symptoms resolved rapidly over 4–6 days followed by complete neurological recovery. In all patients, MRI performed within 1–3 days of onset of encephalopathy demonstrated a symmetrical diffusion-restricted lesion in the splenium of the corpus callosum. Three patients had additional lesions involving other parts of the corpus callosum and adjacent periventricular white matter. These same three patients had mild persisting white matter changes evident at followup MRI, while the other patients had complete resolution of radiological changes. A potential trigger was present in five of the seven cases: Kawasaki disease, Salmonella, cytomegalovirus, influenza B and adenovirus (all n = 1). Elevated white cell count (n = 4), elevated C reactive protein (n = 5) and hyponatremia (n = 6) were commonly observed. CSF was performed in four patients, which showed no pleocytosis. This case series of MERS demonstrates this condition occurs outside of East Asia and is an important differential to consider in children presenting with acute encephalopathy.